Changes in nonfunctional adrenal incidentaloma after COVID-19 infection and a model for predicting benign and malignant adrenal incidentaloma - Chen, Danlei; Zeng, Sheng; Liu, Qian (Frontiers in Endocrinology, 2024)
To compare nonfunctional adrenal incidentalomas (NFAI) in individuals with and without a history of COVID-19 infection, while also establishing predictive models for distinguishing between benign and malignant adrenal incidentalomas (AI).: A retrospective collection of data from patients with AI who underwent surgery and were verified in our hospital between April 2022 and June 2023 was conducted. A total of 121 patients were included in the study. Demographic information, tumor characteristics, functional indicators, and complications were compared among the patients. Statistical analyses utilized the t-test for continuous variables and Pearson chi-square test or Fisher's exact test for categorical variables. Results: Patients with COVID-19 exhibited a higher prevalence of obesity (84.2% vs. 63.3%, P=0.048) and elevated direct bilirubin (DBIL) levels (44.1% vs. 19.2%, P=0.043) compared to those without COVID-19. Moreover, patients with Malignant AI, in contrast to Benign AI, showed higher normal total protein (TP) levels (28.8% vs. 57.1%, P=0.016) and larger tumor sizes (20 vs. 32.5mm, P=0.009). Univariate analysis identified low TP (OR=0.303, 95% CI=0.111-0.825, P=0.020) and tumor size (OR=1.045, 95% CI=1.011-1.080, P=0.009) as potential risk factors for multivariate analysis. A predictive model comprising clinical risk factors (tumor size and low TP) demonstrated an AUC of 0.754 (95% CI, 0.603-0.904) with a sensitivity of 0.75 and specificity of 0.775. The calibration curve revealed a bias-corrected AUC of 0.77. Conclusion ： No discernible differences in the clinical manifestations of adrenal incidentalomas were observed between cases with and without a history of COVID-19 infection. However, AI with larger tumor diameters and lower than normal levels of total protein exhibited a more pronounced malignant potential.